2018
DOI: 10.15537/smj.2018.5.21751
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin and serotonin transporter levels in autistic children

Abstract: ObjectivesTo assess the possible correlation between serotonin and serotonin transporter (SERT) with the autism severity and investigate the association between these parameters in autistic children to assess their possible role for diagnosis of autism severity.MethodsA comparative cross-sectional study was carried out in the Chemistry and Biochemistry Department, College of Medicine, Al-Nahrain University, Baghdad, Iraq while the samples were taken from 60 male autistic children recruited to the Department of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 32 publications
1
34
0
1
Order By: Relevance
“…Half a century ago, elevated whole blood 5-HT (hyperserotonemia) was the first molecular phenomenon found in a subset of ASD subjects, today associated with 25-30% of cases. The fact that hyperserotonemia is not detected in every autistic case is consistent with the correlation of this feature with ASD severity (Abdulamir et al, 2018) and also reveals individual variations in the biological inner management of disturbances impacting the 5-HT system. Along this line, it is worth knowing first that the level of 5-HT contained in blood platelets does not reflect its synaptic concentration.…”
Section: Pivotal Role Of Serotoninsupporting
confidence: 78%
“…Half a century ago, elevated whole blood 5-HT (hyperserotonemia) was the first molecular phenomenon found in a subset of ASD subjects, today associated with 25-30% of cases. The fact that hyperserotonemia is not detected in every autistic case is consistent with the correlation of this feature with ASD severity (Abdulamir et al, 2018) and also reveals individual variations in the biological inner management of disturbances impacting the 5-HT system. Along this line, it is worth knowing first that the level of 5-HT contained in blood platelets does not reflect its synaptic concentration.…”
Section: Pivotal Role Of Serotoninsupporting
confidence: 78%
“…We found a correlation between gut serotonin levels with neurodevelopment scores of ASD children, while serotonin and N-feruloyl serotonin levels were positively correlated with sensory subscales of ABC. Many researches have indicated that the blood levels of serotonin are correlated with autism severity [36]. A Balanced amount of enteric serotonin is bene cial to the functioning of the intestine, nervous system, and gut-brain axis, while excess serotonin may play a harmful role in the progression of ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated blood serotonin (5-HT) levels, and serotonin transporter (SERT) consistently recorded in individuals with ASD [16].…”
Section: Biomarker For Autism Gives Hope For Future Autism Treatmentmentioning
confidence: 99%